Piano sonata no. 19, op. 49, no. 1, edited by Winkler, with Winkler's metronome markings - Beethoven, Ludwig van, 1770-1827 (2025)
Piano sonata no. 19 in G minor, op. 49, no. 1, edited by Winkler, with Winkler's metronome markings